2014
DOI: 10.1007/s00270-014-0927-9
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Factors Influencing the Hemodynamic Behavior of the AAA Stent Grafts: Essentials for the Clinician

Abstract: Endovascular aneurysm repair (EVAR) is considered to be the treatment of choice for abdominal aortic aneurysms (AAA). Despite the initial technical success, EVAR is amenable to early and late complications, among which the migration of the endograft (EG) with subsequent proximal endoleak (Type Ia) leads to repressurization of the AAA sac, exposure to excessive wall stress, and, hence, to potential rupture. This article discusses the influence that certain geometrical factors, such as neck angulation, iliac bif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…This mechanism is supported by our results, where neck angulation was found to be significantly associated with stent-graft surface movement in the multivariate analysis. Displacement forces and stent-graft stability are also related to the iliac fixation [14, 37]. Through distal fixation, different authors have identified the docking area of the modular stent graft limb as a vulnerable region, which seems to be exposed to the highest mechanical stress [31] and surface movement [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism is supported by our results, where neck angulation was found to be significantly associated with stent-graft surface movement in the multivariate analysis. Displacement forces and stent-graft stability are also related to the iliac fixation [14, 37]. Through distal fixation, different authors have identified the docking area of the modular stent graft limb as a vulnerable region, which seems to be exposed to the highest mechanical stress [31] and surface movement [15].…”
Section: Discussionmentioning
confidence: 99%
“…Different mechanisms, such as the radial forces of self-expandable stent-grafts due to oversizing [8, 9] and the pulsatile forces of blood flow [1012], were suggested to be associated with continuous changes in stent-graft position and decreasing apposition of the stent-graft surface, consequentially causing migration over time. In addition, disease progression could trigger and accelerate both mechanisms [13, 14]. Stent-graft dynamics over time are complex and three-dimensional [1517], and not only limited to a one-dimensional, most commonly caudal displacement of the stent-graft, as defined for migration [18].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Georgakarakos et al notes that endovascular treatment of AAAs should not be considered a single step intervention based on preoperative anatomical features alone, but rather that the aorta continues to remodel around the endograft for years after implantation. 5 This concept is essential for the modern vascular surgeon to consider when planning the initial AAA intervention and any subsequent adjunctive procedures to enhance longevity of the repair.…”
Section: Is There Evidence Of Progressive Neck Dilatation?mentioning
confidence: 99%
“…The aim of our study is to identify biomarkers predictive of successful cell treatment in non healing vascular leg ulcers (VLU) using a reproducible technical approach verified in parallel with a deep lab cell characterization. Methods -From an initial cohort of 38 patients, 16 patients affected by non healing VLUs were randomized respectively to gold standard treatment (control arm,5 men 3 women) and to gold standard treatment plus ASCs (experimental arm, 5 men 3 women) sampling according to Coleman's technique 4 . The sample was centrifuged at 1300 r / min for 3 minutes and injected with an 18 G needle into the edges and into the bed of ulcer.…”
mentioning
confidence: 99%